Comparison of cholesterol-lowering effect of β-glucan in cereals and bread - Steneryd, Ellen (SLU/Dept. of Food Science, 2016)
High levels of total- and LDL-cholesterol in blood are risk factors related to cardio-vascular disease. One of several measures to prevent this is consumption of the viscous soluble fibre β-glucan that in high amount is found in oats. In 2006, EFSA approved the health claim that a dose of at least 3 g β-glucan per day maintains normal blood cholesterol concentrations. The cholesterol-lowering properties of β-glucan have been shown to vary based on the processing and use in products. The aim of this literature review was to compare the cholesterol-lowering effect of oat β-glucan in ready-to-eat cereals and bread. These two products are easily accessible and common in the western diet. They can contain β-glucan of the same source but differ in several steps of manufacturing. The cholesterol lowering property of oat β-glucan is primarily affected by the solubility and molecular weight distribution. In bread making, fermentation and the use of flour with low falling number can decrease molecular weight and increase solubility. In the manufacturing extruded ready-to-eat cereals, high molecular weight is retained and solubility increased. One of the possible cholesterol lowering mechanisms of β-glucan is by increased hepatic bile acid production from choles-terol either endogenously synthesized or taken from the circulation. Six studies with ready-to-eat cereals and five studies with bread or muffins, cookies and buns were included for comparison. Eight out of the selected eleven studies reported a significant decrease in total- and LDL-cholesterol. Regarding dose of β-glucan and study subjects, the studies with cereals had more similarities and achieved more consistent results compared to the studies with bread. Ready-to-eat cereals seem to be a more favourable product than bread for oat β-glucan consumption in order to achieve a cholesterol reduction, due to more beneficial effects of processing on molecular weight and solubility of the β-glucan.